Advances in production management systems. innovative production management towards sustainable growth : IFIP WG 5.7 International Conference, APMS 2015, Tokyo, Japan, September 7-9, 2015, Proceedings /: innovative production management towards sustainable growth : IFIP WG 5.7 International Conference, APMS 2015, Tokyo, Japan, September 7-9, 2015, Proceedings. Part II : (2015) - Unknown
No abstract available